SPECIAL NEED EDUCATION TEACHER’S COMPETENCY MASTERY THROUGH TEACHER INTERNSHIP PROGRAM I - Farouq Ghoer, Hilman; Ratnawulan, Teti; Wachyudin, .; Mulyati, Euis (PEOPLE: International Journal of Social Sciences, 2017)
A teacher and prospective teacher of Special Need Education are required to master, understand, and practice 4 (four) teachers’ basic competences covering pedagogy, personality, social and professional competence with various peculiarities of learners, whether with permanent and temporary barriers. In fact, high score for final test does not reflect the four basic competencies. So it needs crucial study. Through R & D method, it is obtained the result that is; the developed instruments in teacher internship program I need to be adjusted to the specialization of the learners; Obstacles that occur that the school’s paradigm still consider the program is identic with PPLK (field practice), whereas teacher internship program is in semester 2, PPLK is in semester 6, the campus parties have not provided yet the theory of the internship program I before the practicing comprehensively. The internships program needs to be adjusted to the schedule of lectures; Designs are expected to be tailored to the specialty of learners (A, B, C), specialized in UNINUS, specialization A and C. To build teacher’s attitude in pedagogic competence; Students experience and gain information about teachers' competencies, teaching and learning process and teacher’s administration; In personality competencies, they acquire a good and flexible personality; for social competence, they gain experience of good relationships with children, parents, and colleagues, and in professional development, they follow the activities and the addition of teacher’s documents.